Islamic countries and Maqasid al-Shariah towards the circular economy. The Dubai case study. - Campra, Maura; Brescia, Valerio; Jafari-Sadeghi, Vahid; Calandra, Davide (European Journal of Islamic Finance, 2021)
This paper aims to explore the economic, social, and environmental policies in Gulf countries. Despite the increased attention paid by scholars on circularity, there is no evidence about the relationship between the circular economy and Islamic countries. Using an explorative case study, this paper benefits from analyzing several information sources underlying the first link between circularity and Islamic countries. After an in-depth literature review, the authors present a useful comparison between the linear and circular economy concepts. Additionally, we emphasize a framework of policies and best practices adopted from Dubai, which merges several approaches applied towards the circular economy. Furthermore, this paper highlights the theoretical link between social entrepreneurs and Islamic pillars based on the Maqasid al-Shariah business model. In conclusion, the article provides useful implications for researchers and practitioners, who in the future aim to investigate the relationship between Islamic systems and the circular economy.